Differences in The Effectiveness of Oxytocin Massage and Major Pectoralist Massage Towards Acceleration of Breast Milk Expenditure in Postpartum Mothers in PMB Ngadila Sobirin Malang District - Yuniar Angelia Puspadewi; Jiarti Kusbandiyah (EMBRIO: Jurnal Kebidanan, 2021)
Breastmilk (ASI) is a staple food that can be given to a newborn for growth and development of the baby for his survival. Therefore, almost 80% of mothers who give birth are able to produce enough milk for the needs of their babies. Psychological factors because there is a belief from the mother that she cannot provide breast milk which will cause a decrease in the hormone oxytocin so that breast milk cannot come out immediately after birth, so the mother takes the decision to give formula milk. The research objective in this study was to analyze the difference in the effectiveness of oxytocin massage and pectoralis major muscle massage on the acceleration of breastfeeding in postpartum mothers. The number of respondents in each group was 20 people with criteria such as postpartum mothers before 2 hours, breastfeeding did not come out at all, mothers gave normal birth. Both groups were checked for the smooth release of breast milk on which day by observation. This study used a true experiment design with a postest-only control design approach. The independent variables in this study were oxytocin massage and pectoralis major muscle massage which was carried out 2 times a day massage with a massage duration of 2-3 minutes for 5 days, while the dependent variable was the speed of expressing breastmilk which occurred on what number of days postpartum. The results showed that the U value was 122 and the W value was 375. When converted to Z value, the value was -2.593. Sig value or P value 0.010 <0.05 means that there is a significant difference between the 2 groups, namely oxytocin massage is more effective in accelerating breastfeeding.